Dementia screening in elderly high-risk patients following heart failure decompensation may predict unfavorable long-term clinical outcomes. (25th November 2020) - Stepien, K; Furczynska, P; Zalewska, M; Nowak, K; Wlodarczyk, A; Owsianka, I; Skorek, P; Zalewski, J; Nessler, J
Abstract: Background: Recently heart failure (HF) has been found to be a new dementia risk factor, nevertheless their relations in patients following HF decompensation remain unknown. Purpose: We sought to investigate whether a screening diagnosis for dementia (SDD) in this high-risk population may predict unfavorable long-term clinical outcomes. Methods: 142 patients following HF decompensation requiring hospitalization were enrolled. Within a median time of 55 months all patients were screened for dementia with ALFI-MMSE scale whereas their compliance was assessed with the Morisky Medication Adherence Scale. Any incidents of myocardial infarction, coronary revascularization, stroke or transient ischemic attack (TIA), revascularization, HF hospitalization and bleedings during follow-up were collected. Results: SDD was established in 37 patients (26%) based on the result of an ALFI-MMSE score of <17 points. By multivariate analysis the lower results of the ALFI-MMSE score were associated with a history of stroke/TIA (β=−0.29, P<0.001), peripheral arterial disease (PAD) (β=−0.20, P=0.011) and lower glomerular filtration rate (β=0.24, P=0.009). During the follow-up, patients with SDD were more often rehospitalized following HF decompensation (48.7% vs 28.6%, P=0.014) than patients without SDD, despite a similar level of compliance (P=0.25). Irrespective of stroke/TIA history, SDD independently increased the risk of rehospitalization due to HF decompensation (HR 2.22, 95% CI 1.23–4.01, P=0.007). Conclusions: As shown for the first time in literature patients following decompensated HF, a history of stroke/TIA, PAD and impaired renal function independently influenced SDD. In this high-risk population, SDD was not associated with patients' compliance but irrespective of the stroke/TIA history it increased the risk of recurrent HF hospitalization. Funding Acknowledgement: Type of funding source: None